Editorial: Evidence-based on health benefits: probiotics, micronutrients, and edible plants - Lee, Learn-Han; Goh, Bey Hing *; Dilokthornsakul, Piyameth; Saokew, Surasak (Frontiers Media, 2023)
Nutrition is critical in preventing, treating, and prognosis acute and chronic disorders. The field of nutritional epidemiology, which has emerged from public health sciences, has been the cornerstone of nutrition research for several decades, significantly influencing dietitian practices and dietary counseling worldwide (1). Evidence-based nutrition involves a conscientious approach, working with patient's preferences and values to help them address physical, mental, and social health challenges by integrating the best available nutrition evidence with clinical expertise. In recent years, there has been growing interest in understanding the therapeutic role of probiotics, micronutrients and bioactive compounds derived from edible plants in various health conditions (2–4).